Applicability of OCO-2 Solar Induced Chlorophyll Fluorescence (SIF) Data for the Estimation of Photosynthetic Activity in Bangladesh - Islam, Mohammad Imrul; Habib, SM Ahsan; Haque, SAM Arif Ul; Sultana, Nasrin; Faisal, BM Refat; Rahman, Hafizur; Sharifee, Mohammad Nur Hossain (Journal of Engineering Science, 2020)
Orbiting Carbon Observatory-2 (OCO-2) is a new satellite of measuring concentrations of carbon, can also provide comparatively higher resolution Solar Induced Chlorophyll Fluorescence (SIF) data which has the potential to directly estimate the photosynthetic activity or gross primary production (GPP). The aim of the present study is to investigate the feasibility of using OCO-2 derived SIF data for the estimation of photosynthetic activity in Bangladesh. To verify the OCO-2 derived SIF data, the present study analyzes the relationship between OCO-2 derived SIF and Moderate Resolution Imaging Spectroradiometer (MODIS) derived GPP for different land cover types for the year 2015 using individual day pixel-based analysis. The relationship between SIF and GPP is found to be good for the mixed vegetation for the data accessed on 01 January and 02 February of 2015 and for the evergreen forest for the data accessed on 14 September of 2015. In contrast, the relationship is not found strong between SIF and GPP for most of the cases. The pixel-based spatial dissimilarity between OCO-2 and MODIS, and spatial distortions of OCO-2 footprints might be the possible reason behind the poor correlation between SIF and GPP found in the present study. Unavailability of the homogeneous OCO-2 derived SIF data in terms of spatial and temporal context is another possible reason behind the weak relationship between SIF and GPP. The sparse spatial coverage and poor relationship to the MODIS derived GPP data declines the reliability of OCO-2 derived SIF data for the estimation of photosynthetic activity in Bangladesh or in other local scale application. Journal of Engineering Science 11(2), 2020, 133-140